A Blockchain-Based Verifiable Decentralized Mechanism for Digital Voting System - Rini Deviani (APTIKOM SUMSEL, 2023)
Digital voting systems have garnered significant attention in recent years due to their potential to increase accessibility and transparency in elections. However, concerns about security, transparency, and verifiability have limited their widespread adoption. This paper proposes a blockchain-based verifiable decentralized mechanism for digital voting systems, aiming to address these concerns. By leveraging blockchain technology, cryptographic techniques, and decentralized consensus, our proposed mechanism offers a secure and transparent platform for conducting digital elections. This paper outlines the architecture, components, and benefits of our system, highlighting its potential to revolutionize the way we conduct elections. The proposed mechanism incorporates advanced encryption algorithms to secure the privacy of individual votes. This privacy-centric approach safeguards voter anonymity while still allowing for transparent verification of the overall election results. Security analysis underscores the effectiveness of the blockchain-based verifiable decentralized mechanism in addressing key concerns surrounding digital voting systems. By leveraging innovative technologies and cryptographic principles, the proposed system exhibits a high degree of resilience, transparency, and protection against potential threats, making it a promising solution for secure and trustworthy digital elections.